Evaluation of Mothers' knowledge of neonatal care who referred to university maternities of Mashhad in 2014 - Rozita Davoodi; Fatemeh Tara; Masoumeh Mirteimouri; Salmeh Dadgar; Robab Latifnejad Roudsari; Azadeh Soltanifar; Shaghayegh Rahmani; Golnaz Sabouri; Maryam Zare Hoseini; Nafiseh Saghafi; Toktam Hoseinnezhad; Mahboubeh Asadi (Mashhad University of Medical Sciences, 2017)
Introduction: Children are important component of future society and providing their health care is a national investment. With regard to close contact between mother and child, so, improving the mothers' knowledge about neonatal care and the risk factors can be effective to prevent neonatal mortality and morbidity. This study was performed with aim to evaluate mothers' knowledge about neonatal care in three educational hospitals of Mashhad University of Medical Sciences. Methods: This cross-sectional study was conducted in 2014 on 784 pregnant women referred to maternity wards of Omolbanin, Emam reza and Ghaem hospitals. The data collection tool was a researcher-made questionnaire on neonatal care. Data were analyzed by SPSS software (version 16) and using t-tests, Chi-square and ANOVA. P< 0.05 was considered significant. Results: The knowledge of 50 mothers (6.4%) about neonatal care was poor, 430 (54.8%) moderate and 295(37.6%) good. The mothers with diploma level education had the highest level of knowledge than other mothers. There was significant relationship between mother's level of education, job and mode of delivery with mothers' knowledge about neonatal care (P=0.005). Conclusion:Due to the effect of mothers' knowledge in the prevention of neonatal disease and mortality, it is better to focus more on educating mothers, especially in the field of mother's diet and exercise, nipple cracking, and safe drugs during breastfeeding for all mothers.